Dynamic communication performance of STTN under various traffic patterns using virtual cut-through flow control - Faisal, Faiz Al; Rahman, M.M. Hafizur; Inoguchi, Yasushi (2014)
Symmetric Tori connected Torus Network (STTN)is a 2D-torus network of multiple basic modules, where each basic module is a 2D-torus network that are hierarchically interconnected for higher-level networks. The static network performance for STTN has already been studied earlier and shown to be good than that of other networks considering very large size networks. In this paper, we evaluate the dynamic communication performance of STTN using the virtual cut through (VCT) flow control under different traffic patterns; and also evaluate the static cost factor for STTN against the most recently adopted 5D Torus network. We have found that with the non-uniform traffic patterns of STTN yields much better performance than that of 2D Torus, 2D Mesh, TESH and TTN networks in terms of network throughput and latency. The static cost factor of STTN is also better than that of 5D Torus network.